Prednosti in slabosti ločitve komercialnega in investicijskega bančništva - Sega, Sanja (Podjetje in delo, 2016)
Almost immediately after the outburst of global financial crisis 2007-2009 the world reacted by enacting numerous regulatory reforms, based on higher capital requirements, regulation of unregulated financial sector entities, more effective supervision, deposit guarantees, and derivatives risk management. Problems associated with banks "too-big-to-fail" or even "too-big-to-bail" which significantly contributed to the outburst and expansion of the financial crisis, are yet to be solved. This article sheds light on post-crisis global (G20), EU, USA and national (GB, Germany, France, etc.) structural banking reforms. It presents legal and constitutional aspects with pros and cons of the separation of commercial and investment banking.
Keywords: bančništvo; banke; ekonomska kriza; investicije; krize